Foreign direct investment, competition and industrial development in the host country - Salvador Barrios Cobos; Holger Görg; Eric Strobl (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper analyses the impact of foreign direct investment (FDI) on the development of local firms. We focus on two likely effects of FDI: a competition effect which deters entry of domestic firms and positive market externalities which foster the development of local industry. Using a simple theoretical model to illustrate how these forces work we show that the number of domestic firms follows a u-shaped curve, where the competition effect first dominates but is gradually outweighed by positive externalities. Evidence for Ireland tends to support this result. Specifically, applying semi-parametric regression techniques on plant level panel data for the manufacturing sector we find that while the competition effect may have initially deterred domestic firms? entry, this initial effect has been outpaced by positive externalities making the overall impact of FDI largely positive in this country.
Keywords: F2; L6; O1; 330; Foreign direct investment; spillovers; industrial development; firm entry; semiparametric estimations; Direktinvestition; Unternehmensentwicklung; Internationaler Wettbewerb; Spillover-Effekt; Markteintritt; Irland